When I Become a Woman with Multiple Roles: A Phenomenological Study of Women's Experiences in Dual Roles and Long-Distance Marriage - Fixi Intansari; Bayu Sekar Larasati; Rizky Aulia Fitriana (Dinasti International Journal of Education Management and Social Science, 2025)
The phenomenon of women undertaking dual roles remains a persistent and multifaceted challenge, particularly for those who are simultaneously fulfilling responsibilities as wives, mothers, professionals, and students. This complexity is further heightened in the context of Long-Distance Marriages (LDM), especially when young children are involved. This study aims to explore the lived experiences of women managing dual roles within the framework of LDM. Employing a qualitative methodology with a phenomenological approach, data were collected through in-depth interviews with women who are engaged in professional work and higher education, while also navigating long-distance marital relationships and caring for preschool-aged children. The findings reveal that women in dual roles frequently experience role conflict, particularly in fulfilling their maternal duties, which often leads to feelings of guilt and anxiety. Moreover, social support plays a significant role in enabling these women to make informed decisions regarding role management and enhances their capacity for self-regulation. The involvement of extended family members during periods of marital separation also serves as a crucial source of childcare support, facilitating the preservation of emotional bonds between mothers and their children.